The legal aid market : challenges for publicly funded immigration and asylum legal representation - Wilding, Jo, 1974- (Bristol : Policy Press, 2021)
Presenting a rare picture of the barristers, solicitors and caseworkers practising immigration law in charities and private firms, this book offers fresh thinking on what has gone wrong in the legal aid market. In doing so, this book examines supply and demand, challenges existing legal aid policy and proposes insights for steps forward.
Command and Control versus Trust -- Poor quality in the market -- Development of a 'lemon market' -- Conclusion -- 8 Why we need to think about systems -- Conclusion -- Peer-review criteria -- civil files -- C. The Work/Assistance -- Appendix: Independent peer-review criteria and guidance -- Peer-review criteria -- civil files -- C. The Work/Assistance -- References -- Index -- Back Cover.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Legal aid -- Great Britain; Legal assistance to immigrants -- Great Britain